Walking hills - Farrell, Cliff (Doubleday Garden City, New York, 1962)
Zulus - that's what they called them, the ragged men and women who came to the Walking Hills for free land promised by the railroad. But the cattlemen had other ideas. They figured the land was theirs, and they weren't aiming to give it up. And then the killing began. Jeff Temple had traded in his scalpel for a gun, but he wanted no part of this fight - until he had no choice. Available only in Western 14.
29209
Keywords: Western